UPAYA DINAS KOPERASI DAN UKM DALAM PEMBERDAYAAN UMKM KERIPIK TEMPE DI DESA KARANGTENGAH PRANDON KABUPATEN NGAWI - Fibra Zelvianagita; Ananta Prathama (Journal Publicuho, 2023)
This study aims to describe the efforts of the Department of Cooperatives and SMEs in empowering tempe chips SMEs in Karangtengah Prandon Village, Ngawi Regency. The research method used in this research is descriptive qualitative research. This research focuses on the efforts of the Department of Cooperatives and SMEs service in empowering tempe chips SMEs in Karangtengah Prandon Village, Ngawi Regency using the basic theory of empowerment according to Mardikanto and Soebianto. Data collection techniques in this study were through observation, in-depth interviews and documentation review. The results showed that the Department of Cooperatives and SMEs in Ngawi Regency had made efforts related to empowering tempe chips SMEs in Karangtengah Prandon Village properly by the main efforts of empowerment according to the theory of Mardikanto and Soebianto namely Human Development, Business Development, Community Development and Institutional Development. Efforts made by the Department of Cooperatives and SMEs in empowerment, namely through various activities so that tempe chips can be more independent and can develop their business. Although in reality, tempe chip SMEs still do not take advantage of the facilities provided by the Department of Cooperatives and SMEs in the context of business development.